1994
DOI: 10.1002/eji.1830240113
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amino acids on agretopes of pigeon cytochrome c‐related peptides specifically bound to I‐A allelic products

Abstract: In our prior study it was demonstrated that residues 46 and 54 on a synthetic peptide, AEGFSYTVANKNKGIT (50V), work as an agretope (site contacts with major histocompatibility complex molecules) and residues 50 and 52 function as an epitope (site contacts with T cell receptor), when tri-molecular complexes are formed among 50V,I-Ab and the T cell receptor. 50V was composed of residues 43 to 58 of pigeon cytochrome c (p43-58) except that the aspartic acid (D) at residue 50 was substituted by valine (V). Substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…We have produced mice expressing covalently bound analogues of Ep (Ep58K and Ep63K) and pigeon cytochrome c-derived peptide PCC (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) , and TCR␣-chain knockout mice were purchased from The Jackson Laboratory (Bar Harbor, ME). All mice were housed under specific pathogen-free conditions in the animal care facility at the Medical College of Georgia (Augusta, GA).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have produced mice expressing covalently bound analogues of Ep (Ep58K and Ep63K) and pigeon cytochrome c-derived peptide PCC (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) , and TCR␣-chain knockout mice were purchased from The Jackson Laboratory (Bar Harbor, ME). All mice were housed under specific pathogen-free conditions in the animal care facility at the Medical College of Georgia (Augusta, GA).…”
Section: Animalsmentioning
confidence: 99%
“…All three hybridomas were also tolerant to covalent A b Ep complex and A b bound with self peptides. The first hybridoma, 2.1.4, recognized the PCC (43-58) peptide or its analogue PCC(50V54A), which had enhanced binding and stimulatory properties over the original PCC peptide (43). The TCR cloned from this CD4 ϩ T cell hybridoma was expressed in vivo using either the CD2 promoter (VA cassette) or genuine TCR promoters (pT␣/pT␤ cassettes) (32,33).…”
Section: Selection and Cloning Of Ag-specific Tcrs From Cd4 ϩ T Cellsmentioning
confidence: 99%
“…1). Because it had been shown that P1 and P9 are critical sites for interaction with I-A b , analogs with substitutions of charged amino acids at P1 or P9 were not examined in the present experiments (7,8,12,13). Fig.…”
Section: Inf Luence Of Single Replacements Of the Core Region Residuementioning
confidence: 99%
“…However, this orientation appears to differ from the model proposed by Jorgensen et al (6), in which the TCR is rotated approximately 90°relative to the peptide-MHC surface. Thus far, no crystal structure of trimolecular complex, including class II molecules, has been determined, and it is unclear whether formation of the trimolecular complex is predicted by a general model demonstrated with a MHC class I molecule or is determined individually by each of the components.In prior studies (7,8), it has been demonstrated that P1 of a pigeon cytochrome c-(43-58) peptide (p43-58) is a main anchor to the I-A molecule and a particular amino acid at the P1 determines allele-specific peptide binding. Hammer et al (9) and Jardetzky et al (10) also showed that the P1 residue of HLA-DR1-binding peptides represents the most important anchor.…”
mentioning
confidence: 99%
See 1 more Smart Citation